2020
DOI: 10.1371/journal.pone.0242451
|View full text |Cite
|
Sign up to set email alerts
|

Changes in care-seeking for common childhood illnesses in the context of Integrated Community Case Management (iCCM) program implementation in Benishangul Gumuz region of Ethiopia

Abstract: Background Integrated Community Case Management (iCCM) is a strategy for promoting access of under-served populations to lifesaving treatments through extending case management of common childhood illnesses to trained frontline health workers. In Ethiopia iCCM is provided by health extension workers (HEWs) deployed at health posts. We evaluated the association between the implementation of iCCM program in Assosa Zuria zone, Benishangul Gumuz region and changes in care-seeking for common childhood illnesses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…There is evidence that ICCM has improved access to appropriate case management, which leads to earlier treatment, fewer severe cases, improved recovery, fewer referrals, and a reduced burden on health service deliveries ( 4 ). Similarly, studies have shown that ICCM can increase coverage of appropriate treatment for childhood illnesses among the poor and can lead to substantial reductions in child mortality ( 7 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that ICCM has improved access to appropriate case management, which leads to earlier treatment, fewer severe cases, improved recovery, fewer referrals, and a reduced burden on health service deliveries ( 4 ). Similarly, studies have shown that ICCM can increase coverage of appropriate treatment for childhood illnesses among the poor and can lead to substantial reductions in child mortality ( 7 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…This could be achieved by re-examining approaches to foster community engagement and empowerment, further decentralisation of curative child health services, intersectoral collaboration and strong leadership. 47 48 Although the Ethiopian PHC model provides a package of basic preventive and curative child health services to rural households, 49 our study found that the coverage of child health services is low and uneven. We also found that curative child health services may not be available in rural facilities, even though they are mandated to provide child health to rural communities.…”
Section: Open Accessmentioning
confidence: 79%
“…The ability to modify existing health-seeking behaviours through expansion of mCCM is not well established. There are several examples of improvement of care-seeking rates following the introduction of iCCM to naïve populations where it was previously effectively non-existent [ 2 , 3 ]. However, recent publications from Malawi [ 22 ] and Rwanda [ 6 ] underscore the difficulty in increasing care-seeking behaviour through support or expansion of established community case management programs.…”
Section: Discussionmentioning
confidence: 99%